Glucose-Induced Transcriptional Hysteresis: Role in Obesity, Metabolic Memory, Diabetes, and Aging - Mobbs, Charles V. (Frontiers in Endocrinology, 2018)
During differentiation transient inducers produce permanent changes in gene expression. A similar phenomenon, transcriptional hysteresis, produced by transient or prolonged exposure to glucose, leads to cumulative, persistent, and largely irreversible effects on glucose-regulated gene expression, and may drive key aspects of metabolic memory, obesity, diabetes and aging, and explain the protective effects of dietary restriction during aging. The most relevant effects of glucose-induced transcriptional hysteresis are the persistent effects of elevated glucose on genes that control glucose metabolism itself. A key observation is that, as with the lac operon, glucose induces genes that promote glycolysis, and inhibits gene expression of alternative metabolic pathways including the pentose pathway, beta oxidation, and the TCA cycle. A similar pattern of metabolic gene expression is observed during aging, suggesting that cumulative exposure to glucose during aging produces this metabolic shift. Conversely, dietary restriction, which increases lifespan and delays age-related impairments, produces the opposite metabolic profile, leading a shift away from glycolysis and toward the use of alternative substrates, including lipid and ketone metabolism. The effect of glucose on gene expression leads to a positive feedback loop that leads to metastable persistent expression of genes that promote glycolysis and inhibits alternative pathways, a phenomenon first observed in the regulation of the lac operon. On the other hand this pattern of gene expression can also be inhibited by activation of PPAR transcription factors, which promote beta oxidation and inhibit metabolism of glucose-derived carbon bonds in the TCA cycle. Several pathological consequences may arise from glucose-induced transcriptional hysteresis. First, elevated glucose induces glycolytic genes in pancreatic beta cells, which induces a semi-stable persistent increase in insulin secretion, which could drive obesity and insulin resistance, and also due to glucose toxicity could eventually lead to beta cell decompensation and diabetes. Diabetic complications persistent even after complete normalization of glucose, a phenomenon known as metabolic memory. This too can be explained by persistent bistable expression of glucose-induced glycolytic genes.